Animated Powtoon-Based Video to Improve the Ability to Understand Sound Science - Solehah, Nur Faridatus; Setiawan, Deni (Postgraduate, University of Mataram, 2023)
Sound is one of the most critical components of singing. A lack of sound understanding can affect students' ability to sing due to the lack of use of learning media in class. The study aimed to determine the effectiveness and feasibility of Powtoon-based animated video learning media on singing abilities in third-grade students using the 10-step Research and Development (R&D) research method developed by Borg and Gall. Data collection techniques using observation, interviews, questionnaires, and documentation. The results of product data analysis in the form of learning media validation were carried out by experts in the field of materials and media with a percentage of 83.75% and 87.5% with the criteria of